Sistem Pendukung Keputusan Menerapkan Metode Profile Matching Sebagai Alternatif Penentuan Minyak Goreng Terbaik - Andini Dwi Putri; Arie Rafika Dewi (Jurnal Teknologi Sistem Informasi dan Sistem Komputer TGD, 2023)
Cooking oil is one of the products of human needs. Along with the times, there have been many cooking oil management companies that issue various types of cooking oil with different brands. So far, most people only choose the best cooking oil products based on well-known company brands and also based on the price of the cooking oil product itself without looking at the composition of the cooking oil product. As a result, there is often an inappropriate selection of cooking oil because it only refers to price criteria and well-known products. The purpose of this study is to find out which cooking oil product is the best that can be consumed by consumers based on calculations using the profile matching method. The profile matching method was chosen in this study because it is able to select the best alternative from a number of predetermined alternatives. The results of this study using the profile matching method produce more accurate cooking oil data, so that consumers can choose which cooking oil product is the best.